Christianity and Public Culture in Africa - Haynes, Jeffrey (A journal of church and state, 2012)
The role of religion in the public realm in sub-Saharan Africa (henceforward, Africa) is controversial. In order to understand the role of religion in political and social discourse in contemporary Africa—that is, as an ideology of attempted hegemonic control, on the one hand, and as a mobilizing vehicle of community organization to help fend off that control, on the other—scholars have pointed to the importance of the colonial era. During that period, both Christianity and Islam developed and spread as major regional religions, with variable impacts on both politics and society.